1991
DOI: 10.1111/j.1365-2222.1991.tb03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of haptoglobin level to FEV1, wheezing, bronchial hyper‐responsiveness and allergy

Abstract: The relationships of haptoglobin level to respiratory and allergic parameters have been assessed in an epidemiological study conducted in a working population surveyed twice 5 years apart. At the first survey conducted in 892 working men, haptoglobin level was significantly related to FEV1 (r = -0.18; P less than 0.001) and smoking habits. After adjustment for smoking, a history of wheezing was significantly related to lower haptoglobin level. A second survey conducted in 304 men of the original sample 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Kauffmann et al found a negative association between FEV 1 and haptoglobin levels in men. 11 In line with this result, Dahl et al reported that a lower FEV 1 and increased risk of chronic obstructive pulmonary disease were associated with increased plasma fibrinogen levels. 12 Finally, Engström et al showed in men that the FVC was inversely associated with levels of inflammation sensitive plasma proteins (fibrinogen, a 1 -antitrypsin, haptoglobin, ceruloplasmin, and orosomucoid).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kauffmann et al found a negative association between FEV 1 and haptoglobin levels in men. 11 In line with this result, Dahl et al reported that a lower FEV 1 and increased risk of chronic obstructive pulmonary disease were associated with increased plasma fibrinogen levels. 12 Finally, Engström et al showed in men that the FVC was inversely associated with levels of inflammation sensitive plasma proteins (fibrinogen, a 1 -antitrypsin, haptoglobin, ceruloplasmin, and orosomucoid).…”
Section: Discussionmentioning
confidence: 76%
“…Systemic inflammation is also a possible element in the link between respiratory impairment and cardiovascular events. Reduced lung function has been associated with various inflammation sensitive plasma proteins [11][12][13] but, to date, only one study has reported an association between lung function and CRP levels. 14 Although bronchial hyperresponsiveness (BHR) is known to be linked to decline in respiratory function, 15 16 only limited data are available as to whether BHR is associated with systemic inflammation, and the relationship between BHR and CRP levels has never been investigated.…”
mentioning
confidence: 99%
“…The association between FEV 1 and CRP found in this study is consistent with previous studies which found a relationship between lung function and other markers of systemic inflammation. Kauffmann et al [65] found a negative association between FEV 1 and haptoglobin level in men. Dahl et al [66] reported that lower FEV 1 and increased risk of chronic obstructive pulmonary disease were associated with increased plasma fibrinogen levels.…”
Section: Discussionmentioning
confidence: 96%
“…Kauffmann et al [65] found a positive relation in man between BHR and haptoglobin levels, and Tusoda et al [74] recently reported a positive association in pregnant women between BHR and some cytokines -including IL-6 and granulocytemacrophage colony stimulating factor. Recently, the Buyukozturk et al [75] study demonstrated that acute phase reactant serum amyloid A is raised in patients with asthma, which may indicate the presence of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a correlation between systemic inflammatory markers and decline in forced expiratory volume in one second (FEV1) [1], as well as increased bronchial reactivity [2]. An inflammatory process may also affect the alveolar system in the lungs, but to date, only a few studies have shown a relationship between inflammatory markers in the blood and level of gas exchange in the lungs [3,4].…”
mentioning
confidence: 99%